Studies on Antibacterial Activity and Brine Shrimp Toxicity of Leaf Extract of Cassia grandis - Awal, MA; Ashrafuzzaman, Syed; Haque, E Ekramul (Bangladesh Journal of Medical Microbiology, 2009)
Antibacterial activity and toxicity of ethanol extract of Cassia grandis leaves to Brine Shrimp was evaluated. Five Gram-positive and 4 Gram-negative bacteria, namely Sarcina lutea, Bacillus megaterium, Bacillus subtilis, Streptococcus ß-haemolyticus, Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, Salmonella typhi and Klebsiella pneumoniae were tested using disc diffusion method. The extract was inactive at the concentration of 30 μg/disc but exhibited moderate to good activity at concentration of 200 μg/disc against the tested bacteria. In Brine Bhrimp lethality bioassay test, it was observed that LC50 value of the extract was 10.68 μg/ml. From these findings, it is indicative that C. grandis may be useful against microbial diseases. Key words: Antibacterial activity, Brine shrimp, Cassia grandis doi: 10.3329/bjmm.v3i1.2966 Bangladesh J Med Microbiol 2009; 03 (01): 17-19